Ontological materialism and politics in Spinoza, Deleuze and Guattari. [Spanish] (2004)
Politics is inseparable from ontology. Every ontology is political and every politics is itself an ontology. The reciprocal relationship between ontology and politics can be identified as the question of their “parallelism”. This parallelism of the ontological and the political finds its first theoretical formulation in the thought of Spinoza and is later rehabilitated by Deleuze and Guattari in their own philosophy in the form of a radical materialism, an “ontological materialism”.